2022
DOI: 10.3390/healthcare10030532
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression among Psychiatric Healthcare Workers during the COVID-19 Pandemic: A Malaysian Perspective

Abstract: The psychological distress reported among frontline healthcare workers (HCWs) is concerning. Little is known about the mental health of non-frontline, psychiatric HCWs, who play a central role in handling the mental health crisis during the COVID-19 pandemic. This study aimed to examine the prevalence of anxiety and depression among psychiatric HCWs and evaluate its association with socio-demographic, socio-economic, work-related factors and coping strategies. The authors proposed a cross-sectional study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
2
19
1
Order By: Relevance
“…When we stratified the respondents according to age, sex, and type of job, there were no significant differences in psychological distress. Our findings were in contradiction with previous studies [ 47 ]; however, they were aligned with [ 19 ]. Therefore, our findings suggested that age, sex, or type of job were not protective factors for psychological distress.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…When we stratified the respondents according to age, sex, and type of job, there were no significant differences in psychological distress. Our findings were in contradiction with previous studies [ 47 ]; however, they were aligned with [ 19 ]. Therefore, our findings suggested that age, sex, or type of job were not protective factors for psychological distress.…”
Section: Discussioncontrasting
confidence: 99%
“…Zhang et al [ 12 ] asserted that it was crucial to determine factors associated with the psychological distress of front liners, with past studies reporting that psychological constructs, such as psychological flexibility, psychological mindedness, mindfulness, and coping styles, were among protective factors for psychological distress [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Psychological flexibility refers to flexible psychological reactions in order to confront distress and increase capacity to accept the present moment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-quality global data on mental health for vulnerable populations during and after the COVID-19 pandemic is needed. 56 Psychosocial measures of population should be priority for mental health services, 57 mental health interventions during and after the COVID-19 pandemic should be highlighted on international and national public health agendas to improve overall wellbeing. 58 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, health professionals have been directly involved with their COVID-19 patients at different stages—diagnosis, treatment, care, and in the process of death—as family members were unable to accompany COVID-19 patients, who ended up dying alone. Because of this, they are more vulnerable to psychological disorders, such as anxiety [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%